2013
DOI: 10.1016/j.ijsu.2013.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the impact of an ageing population on complication rates and in-patient length of stay

Abstract: Increasing age is associated with increased complication rates and increased hospital length of stay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
25
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 12 publications
1
25
0
Order By: Relevance
“…This effect of age on complication rates is consistent with reports from previous studies. 3 , 23 , 29 The results of the present study are in accordance with those of Saltzman et al 30 who reported on 111 patients who had a mean age of 74 years who underwent primary TSA and found that 25% of patients developed any complication, with 9% major and 20% minor complications, including pulmonary embolus, renal insufficiency, asystole, and transfusion. However, our study differs from Ricchetti et al 31 who reported on the 90-day outcomes of 40 patients who were 80 years or older and 46 patients who were less than age 70 years who underwent TSA.…”
Section: Discussionsupporting
confidence: 92%
“…This effect of age on complication rates is consistent with reports from previous studies. 3 , 23 , 29 The results of the present study are in accordance with those of Saltzman et al 30 who reported on 111 patients who had a mean age of 74 years who underwent primary TSA and found that 25% of patients developed any complication, with 9% major and 20% minor complications, including pulmonary embolus, renal insufficiency, asystole, and transfusion. However, our study differs from Ricchetti et al 31 who reported on the 90-day outcomes of 40 patients who were 80 years or older and 46 patients who were less than age 70 years who underwent TSA.…”
Section: Discussionsupporting
confidence: 92%
“…Population aging has raised great challenges to health policies and services ( 1 ), and aging may pose multiple adverse influences on people, increasing morbidity, disability, mortality, and length of hospital stay ( 2 ). Skeletal muscle atrophy can be observed in the aged people due to causes such as neuromuscular disorders, disuse, and aging ( 3 ).…”
mentioning
confidence: 99%
“…The number of unscheduled emergency department visits by this population has increased by 30% during the last 10 years [ 2 ]. Aging populations have increased the number of older patients presenting for emergency surgery, with patients over 60 representing greater than 30% of all emergency general surgery cases [ 3 ]. Given the significant proportion of older patients in the population, it is important to determine the impact of older age on healthcare outcomes.…”
Section: Introductionmentioning
confidence: 99%